Épisodes de la réception : le partimen d’En Coyne e d’En Raymbaut (BdT 392. 29), ses auteurs et son public (avec une nouvelle édition critique du texte) - Federico Saviotti (Revue des Langues Romanes)
BdT 392.29 is a bilingual Occitan-French partimen between the troubadour Raimbaut de Vaqueiras and the trouvère Conon de Béthune. A close investigation of its language, style, contents, contexts of composition and reception leads to reaffirm that both of the poetic voices belong to real authors, against the hypothesis that this debate should be considered as a “fictional tenso” composed by Raimbaut alone. Through the analysis of the varia lectio it has been possible to check the different audiences’ attitudes (from Constantinople to the Veneto and the Languedoc, between 13th and the beginning of 14th centuries) towards the plurilingual nature of the text and to set the stages for a new critical edition of the poem.